2009
DOI: 10.1002/jhet.18
|View full text |Cite
|
Sign up to set email alerts
|

The synthesis of 4‐(3,3‐dimethyl‐3H‐pyrrolo[2,3‐f]quinolin‐2‐yl)pyrazoles and 4‐(3,3‐dimethyl‐3H‐pyrrolo[3,2‐h]quinolin‐2‐yl)pyrazoles

Abstract: in Wiley InterScience (www.interscience.wiley.com).5-Hydrazinoquinoline and 8-hydrazinoquinoline were converted via Fischer syntheses with 3-methylbutan-2-one into pyrido-indolenines 2,3,3-trimethyl-3H-pyrrolo[2,3-f]quinoline 7 and 2,3,3-trimethyl-3H-pyrrolo[3,2-h]quinoline 11, respectively. Exposure of the indolenines to the Vilsmeier reagent produced aminomethylene-malondialdehydes 8 and 12, which reacted with hydrazine or arylhydrazines to give 4-(3H-pyrrolo[2,3-f]quinolin-2-yl)-and 4-(3H-pyrrolo[3,2-h]quin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0

Year Published

2009
2009
2014
2014

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 5 publications
0
11
0
Order By: Relevance
“…1,3‐Dialdehydes represent interesting building blocks for the synthesis of various heterocyclic ring systems, which often show high biological activities . As in our previous work , the reaction of monosubstituted hydrazines with aminomethylene malondialdehyde 15 resulted in the efficient formation of pyrazoles 16a , 16b , 16c , 16d , 16e , 16f , with migration of the double bond to reform the imine unit (Scheme ).…”
Section: Resultsmentioning
confidence: 69%
See 1 more Smart Citation
“…1,3‐Dialdehydes represent interesting building blocks for the synthesis of various heterocyclic ring systems, which often show high biological activities . As in our previous work , the reaction of monosubstituted hydrazines with aminomethylene malondialdehyde 15 resulted in the efficient formation of pyrazoles 16a , 16b , 16c , 16d , 16e , 16f , with migration of the double bond to reform the imine unit (Scheme ).…”
Section: Resultsmentioning
confidence: 69%
“…We have shown previously that the reaction of 2,3,3‐trimethyl‐3 H ‐indoles with the Vilsmeier reagent, producing aminomethylene malondialdehydes, for example, 11 , is a general process, by demonstrating the transformation using variously substituted 2,3,3‐trimethyl‐3 H ‐indoles . Additionally, we have described a simple and straightforward preparation of 4‐(2,3,3‐trimethyl‐3 H ‐indol‐2‐yl)‐substituted pyrazoles by condensation of these aminomethylene malondialdehydes with hydrazine and arylhydrazines (Scheme ). Recently, other workers used the original aminomethylene malondialdehyde 11 in a similar way, in reactions with hydrazides giving 4‐(2,3,3‐trimethyl‐3 H ‐indol‐2‐yl)‐substituted N ‐acyl‐ and N ‐thioacylpyrazoles .…”
Section: Introductionmentioning
confidence: 92%
“…We recently described the reaction of indolenines 7 and some pyridoindolenines, with the Vilsmeier reagent formed from N,N ‐dimethylformamide and phosphorus oxychloride to produce aminomethylene malondialdehydes such as 8 . Additionally, we showed that these intriguing polyfunctional compounds reacted well with hydrazine or arylhydrazines to produce corresponding pyrazoles 9 , with migration of the exocyclic double bond back into the pyrrole ring, thus restoring the indolenine structure from which the sequence started (Scheme ).…”
Section: Introductionmentioning
confidence: 98%
“…1 , is a general process, by demonstrating the transformation using variously substituted 2,3,3‐trimethyl‐3 H ‐indoles . Additionally, we have described a simple and straightforward preparation of 4‐(3,3‐dimethyl‐3 H ‐indol‐2‐yl)‐substituted pyrazoles 2 by condensation of these aminomethylene malondialdehydes with hydrazine and aryl hydrazines (Scheme ).…”
Section: Introductionmentioning
confidence: 98%